Cognitive poetics and creative practice: beginning the conversation. Issue 1 (2nd January 2018) - Scott, Jeremy
ABSTRACT: This article sits on the critical-creative boundary and draws upon aspects of the field of cognitive poetics – the principled study of what happens in the mind as readers read – to explore how an understanding of these processes might benefit the creative writer. The paper is pioneering in that it considers the implications of cognitive poetic approaches for the 'mechanics' of prose fiction explicitly in terms of creative practice rather than from the perspective of the stylistician or literary critic. It is in providing a principled and rigorous account of the way readers read that cognitive poetics has much to offer the writer. Indeed, the article will argue that writing and reading, rather than being separate activities, should be seen as interrelated positions along a cline.